The Haunting Past: Exploring Jude’s Trauma and Identity in Hanya Yanagihara’s A Little Life - Viitala, Lotta (My University, 2024)
In this thesis, I scrutinize Hanya Yanagihara’s novel A Little Life (2015) from psychoanalytic approach, focusing on trauma and identity studies. I apply Cathy Caruth’s trauma theories and draw insights from Erving Goffman’s studies on disability and stigma. Caruth’s and Goffman’s theories are utilized to examine the protagonist, Jude, and the profound impact of trauma on his behavior, thought, and identity. I contend that Jude’s self-perception is primarily formed by his trauma, and the childhood abuse he has endured has left enduring physical and mental scars. Furthermore, I explore how Jude’s trauma and identity are intricately interwoven, rendering them seemingly inseparable. Through the lens of social identity and relationships, I explore trauma’s role in shaping the protagonist’s experience, and I discuss disability as a stigmatized aspect within the novel. Despite Jude’s endeavors to suppress his traumatic past, reminders persist, exacerbating mental health struggles and fostering a sense of isolation for him. Consequently, as I discuss, he grapples with feelings of inadequacy and unworthiness, burdened by guilt and stigma.
Keywords: Hanya Yanagihara, A Little Life, psychoanalysis, trauma, identity, stigma